2012
DOI: 10.4278/ajhp.090805-quan-253
|View full text |Cite|
|
Sign up to set email alerts
|

Medical Cost Savings for Participants and Nonparticipants in Health Risk Assessments, Lifestyle Management, Disease Management, Depression Management, and Nurseline in a Large Financial Services Corporation

Abstract: Medical cost savings exceeded program costs in a wide variety of health and productivity management programs by the second year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…Other reviews by Serxner and colleagues 54,55 are cited as references in this paper. Lerner et al found few methodologically strong studies focused on economic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Other reviews by Serxner and colleagues 54,55 are cited as references in this paper. Lerner et al found few methodologically strong studies focused on economic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This being said, positive workplace wellness ROI studies have been published related to absenteeism and disease management (Aldana et al, 2005 ; Baicker, Cutler, & Song, 2010 ; Chapman, 2012 ; Pellitier, 2009 ; Serxner, Alberti, & Weinberger, 2012 ). A systematic review and analysis of published workplace health-promotion research indicated that positive clinical and cost-saving outcomes were mostly due to disease management programs (Chapman, 2012 ; Pellitier, 2009 ; Serxner et al, 2012 ). A quasi-experimental study investigating the effectiveness of health and productivity management (HPM) found a cost-saving ROI during years 2 and 3, but with a slighter decrease (Serxner et al, 2012 ).…”
mentioning
confidence: 99%
“…A systematic review and analysis of published workplace health-promotion research indicated that positive clinical and cost-saving outcomes were mostly due to disease management programs (Chapman, 2012 ; Pellitier, 2009 ; Serxner et al, 2012 ). A quasi-experimental study investigating the effectiveness of health and productivity management (HPM) found a cost-saving ROI during years 2 and 3, but with a slighter decrease (Serxner et al, 2012 ). The HPM consisted of HRAs, screenings, and disease management for those with high risk factors.…”
mentioning
confidence: 99%
“…Payers, from the US Government to third-party private insurers and employers, are looking to this kind of big data analysis to inform coverage, decisions, regulatory actions, and policymaking decisions. [1][2][3][4][5] Exploration of large datasets requires access to specialized expertise, programmers, and computing unavailable to clinicians in daily practice. Physician professional organizations, on behalf of their members, have the resources to engage in analysis of these data and advocate for value and quality.…”
mentioning
confidence: 99%